Multifunctional cubic liquid crystalline nanoparticles for chemo- and photodynamic synergistic cancer therapy. Issue 5 (21st April 2020) - Jenni, Sébastien; Picci, Giacomo; Fornasier, Marco; Mamusa, Marianna; Schmidt, Judith; Talmon, Yeshayahu; Sour, Angélique; Heitz, Valérie; Murgia, Sergio; Caltagirone, Claudia
Abstract : Multifunctional lipidic cubic liquid crystalline nanoparticles for potential cancer therapy were engineered by conjugating a porphyrin-based photosensitizer to the block copolymer Pluronic F108 and loading them with the antineoplastic drug Docetaxel. Abstract : With the aim of engineering multifunctional nanoparticles useful for cancer therapy, a diketopyrrolopyrrole-porphyrin based photosensitizer was here conjugated to a block copolymer (Pluronic F108), and used to stabilize in water lipidic cubic liquid crystalline nanoparticles (cubosomes), also loaded with the antineoplastic agent docetaxel. The physicochemical characterization by SAXS, DLS, and cryo-TEM demonstrated that the formulation consisted of cubosomes, about 150 nm in size, possessing a bicontinuous cubic structure (space group Pn 3 m ). The cellular imaging experiments proved that these nanoparticles localized in lysosomes and mitochondria, while cytotoxicity tests evidenced a slight but significant synergistic effect which, after irradiation, increased the toxicity induced by docetaxel alone, allowing further reduction of cell viability.